Lifestyles and entrepreneurial orientation of future teachers - Bjekić Dragana R.; Zlatić Lidija Đ. (University of Kragujevac - Faculty of Pedagogy, Užice, 2023)
Based on the importance of the teacher's directions to developing pupils' value systems, value orientation, and professional orientation, the connection between future teachers' value orientation and their entrepreneurial orientation, as an important component of entrepreneurial behaviour, is considered in the paper. The scale of lifestyles and the scale of entrepreneurial orientation are applied. The sample consists of 258 university students from three faculties with departments of education of preschool teachers, class/primary school teachers, and subject teachers. The following results were obtained: the students preferred the working lifestyle, the utilitarian lifestyle, the esthetic lifestyle, and the hedonistic lifestyle (these are the lifestyles oriented toward one's wellbeing) more than the others, and they preferred a lifestyle of orientation toward power and respect less than the others. They assessed their entrepreneurial orientation as moderate. Entrepreneurial orientation as a composite measure and some of its separated components - readiness for risk and competitiveness correlated positively with the level of preferring two lifestyles: the lifestyle of orientation toward power and respect and the lifestyle of Prometheus activism; proactivity correlated with Prometheus activism and altruistic lifestyles, that is, with prosocial lifestyles. The main conclusion is that systematic educational interventions for the development of the entrepreneurial orientation of future teachers are necessary. These interventions should be integrated into future teacher pre-service education both directly as programmes of entrepreneurship education and indirectly as activities enhancing lifestyles and value orientation, which are formative for their professional engagement in the educational process.